Post-processing of DLP-printed denture base polymer: Impact of a protective coating on the surface characteristics, flexural properties, cytotoxicity, and microbial adhesion. Issue 12 (December 2022) - Dai, Jingtao; Luo, Ke; Spintzyk, Sebastian; Unkovskiy, Alexey; Li, Ping; Xu, Shulan; Fernandez, Pablo Kraemer
Abstract: Objectives: To investigate the effect of a protective coating on the surface characteristics, flexural properties, cytotoxicity, and microbial adhesion of vat-photopolymerization additive-manufacturing denture base polymers. Methods: The specimens were additively manufactured using digital light processing (DLP). Specimen surfaces were coated with the same printed resin, and mechanical polishing was used for comparison. Surface topography, arithmetical mean height (Sa ), and water contact angle values were measured. Furthermore, flexural strength (FS)/modulus and fractography were evaluated. Also, cytotoxicity was evaluated by an extract test. Finally, an adhesion test was used to investigate the adhesion of mixed oral bacteria to the specimens. Results: The Sa values in the polished (0.26 ± 0.08 µm) and coated (0.38 ± 0.14 µm) groups were significantly lower than in the untreated (2.21 ± 0.42 µm) and control (2.01 ± 0.37 µm) groups. The coating treatment resulted in a higher FS compared to the untreated surface ( p = 0.0002). After the coating treatment, no significant differences were found in relative cell viability between the groups ( p > 0.05). The quantitative results showed significantly higher bacterial adhesion in the untreated group than in the polished ( p = 0.0047) and coated ( p < 0.0001) groups. Significance: The surface characteristics and flexural properties were optimized by the protective coating. Also, the protective coating did not adversely affect cytocompatibility. Moreover, the coating treatment could effectively decrease oral bacteria adhering to the surfaces. Therefore, the protective coating treatment can be a less time-consuming alternative to mechanical polishing as a post-processing procedure for the digital denture. Highlights: Surface roughness was significantly decreased by the coating treatment. The coating treatment resulted in a higher flexural strength than the untreated surface. The protective coating did not adversely affect cytocompatibility. The coating treatment could effectively decrease oral bacteria adhering to the surfaces. The protective coating treatment can be a valid alternative to mechanical polishing as a post-processing procedure for an additively manufactured denture.